Analysing the Construction of the Social Status of Teaching from the Visual Rhetorics of Chilean Digital Press - Roa-Tampe, Karin; Oyarzún, Juan de Dios; Caro-Zúñiga, Diego; Zenteno-Silva, Catalina; Fernández Cambiaso, María Sofía (Journal of Education Culture and Society, 2026)
Aim. This study examines how the teaching profession is visually narrated in Chilean digital news media, and how these rhetorics contribute to the construction of teachers’ social status. Situated within global concerns regarding teacher recruitment and retention, the study focuses on media imagery as a key site where the social status of professions is produced and propagated. Methods. The methodology is based on the visual rhetoric approach and involves the semiological analysis of a sample of 68 images published between 2022 and 2023 in two major Chilean digital news outlets. The analytical procedure comprised three phases: a denotative and descriptive analysis, a connotative analysis, and a final phase in which visual rhetorics were identified. Results. The findings reveal three visual rhetorics: (a) teachers as educators, predominantly women engaged in traditional classroom roles centred on care and proximity; (b) teachers as union activists, largely narrated by men occupying leadership and spokesperson positions; and (c) teachers as undifferentiated protagonists, presented through portrait-style images that lack clear professional context, expertise, or collegiality. Conclusions. This study is among the first to examine how visual rhetorics in the digital press shape the social status of teachers. These visual rhetorics contribute to the symbolic construction of the teaching profession’s social status by reinforcing gendered divisions, emphasising care and activism over technical expertise, and silencing collaborative and specialised dimensions of professional practice. The findings highlight the role of press visual rhetorics in sustaining limited and traditionalised understandings of teaching, and, to some extent, to education, which contribute to the construction and dissemination of a diminished social status of the profession.